Research Trend of Studies Regarding the Change and Treatment of the Skin on Pregnant Women in the Last Decade: A Systematic Review and Bibliometric Analysis - Nauli, Agnes; Dalimunthe, Dina Arwina (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2023)
Background: The number of publications related to the change and treatment of the skin in pregnant women in the last decade has significantly grown. To date, however, a study offering comprehensive information related to the change and treatment of the skin in pregnant women has not been conducted or found in an electronic journal or proceeding. The purpose of this study is to present a bibliographic and bibliometric review of the numerous documents studying the skin of pregnant women. Methods: A systematic review involving bibliometric analysis with quantitative method was performed to carry out this studywhich 198 eligible documents from the Scopus database published in the period of 2013–2022 were used as research materials. Result: Results revealed that the publication and development of studies related to the change and treatment of the skin in pregnant women slightly soared from 2013 until 2022. Meanwhile, the citation development of he studies regarding the change and treatment of the skin in pregnant women tended to moderately decrease between 2013 and 2022. Additionally, influential documents, authors, countries, affiliations, and sources contributed to the development of studies related to the change and treatment of the skin in pregnant women. Discussion: In particular, this study informs us that the publication and development of studies related to the change and treatment of the skin in pregnant women slightly soared from 2013 until 2022. Most pregnant women undergo a skin change. This study implies that women must treat a skin change when they are pregnant.